Pengaruh Beban Pendinginan Terhadap Temperatur Sistem Residential Air Conditioning Hibrida Dengan Kondensor Dummy Tipe Multi Helical Coil Menggunakan Refrigeran Hidrokarbon - Adha, Aidil; Aziz, Azridjal; Mainil, Rahmat Iman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
One way to save the energy is to improve the energy efficiency with combining two different equipmentsbecome one new double-function or hybrid equipment. Hybrid air conditioning can improve energy efficiency byremoving waste heat to the environment through condenser for heating water. The objective of this experimentalstudy is to investigate the effect of cooling load to system temperature of vapor-compression cycle hybrid airconditioning system with multi helical tipe of dummy condenser. The test was conducted with several coolingload variations (0, 1000, 2000 and 3000 Watt) as residential cooling load simulation. The result showed that therefrigerant temperature while using HCR-22 was obtained about 67.47 Â°C to 72.93 Â°C. The temperature ofrefrigerant was increased as well as the applied cooling load to be increased. The temperature of refrigeranthad more heat which to be absorbed and released into the environment so that the produced water temperaturewasalso increased. Hot water temperature of the ACWH system using HCR-22 refrigerant was obtained about41.01-44.96 ËšC.Keywords : hybrid air conditioning, dummy condenser, hydrocarbon refrigerant HCR-22, cooling load.